Extracellular electron uptake from carbon-based π electron surface-donors: Oxidation of graphite sheets by: Sulfobacillus thermosulfidooxidans probed by Raman and FTIR spectroscopies - Tselios, Charalampos; Papageorgiou, Marios; Varotsis, Constantinos (My University, 2019)
In this work we report Raman and FTIR evidence for extracellular electron uptake by Sulfobacillus thermosulfidooxidans from the solid phase carbon-based π-electron donor surface of graphite sheets. The primary step in the reaction is the intercalation of water on the surface of graphite followed by the formation of EPS and proceeds to form graphite oxide (GO) with a Raman ID/IG = 0.3 ratio which represents the highest defect content in the carbon lattice reported by bio-oxidation process. We propose and discuss a direct extracellular electron transfer mechanism via outer membrane redox proteins for the electron transfer.
Keywords: Electron Transport Complex IV; Heme; Heme a3